2016
DOI: 10.1016/j.bjhh.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A new index to discriminate between iron deficiency anemia and thalassemia trait

Abstract: BackgroundThe most common microcytic and hypochromic anemias are iron deficiency anemia and thalassemia trait. Several indices to discriminate iron deficiency anemia from thalassemia trait have been proposed as simple diagnostic tools. However, some of the best discriminative indices use parameters in the formulas that are only measured in modern counters and are not always available in small laboratories.The development of an index with good diagnostic accuracy based only on parameters derived from the blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 16 publications
0
52
0
Order By: Relevance
“…The Youden's index considers both sensitivity and specificity and provides an appropriate measure of the overall validity of the index or technique [23]. Matos et al, [6] reported that its sensitivity was 99.3%, Specificity 76.7% and YI was 76.0%, and the evaluation of this index by Arora et al, [22] showed high sensitivity to detect IDA (98.81%), excellent diagnostic accuracy and showing good applicability as screening tool in clinical practice. On the other hand Sirdah et al, [5] [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Youden's index considers both sensitivity and specificity and provides an appropriate measure of the overall validity of the index or technique [23]. Matos et al, [6] reported that its sensitivity was 99.3%, Specificity 76.7% and YI was 76.0%, and the evaluation of this index by Arora et al, [22] showed high sensitivity to detect IDA (98.81%), excellent diagnostic accuracy and showing good applicability as screening tool in clinical practice. On the other hand Sirdah et al, [5] [25].…”
Section: Discussionmentioning
confidence: 99%
“…These confirmatory tests could be limited for mass screening programs, due to financial causes, especially in developing and poor countries with restricted resources [4] [5]. The development of indices with good diagnostic accuracy based on parameters derived from the blood cell counters would be useful in the clinical routine [6]. Accurate diagnosis of hypochromic microcytic anemia is an everyday concern for physicians; for appropriate treatment and prevention of disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other data suggest that MicroR could be of potential interest to detect beta‐thalassemia minor in patients, but a ROC curve analysis supports MCV to be a better marker (respectively, AUC = 0.89 and 0.92, Figure ). MicroR/%HypoHe ratio is not accurately enough to discriminate beta‐thalassemia minor and iron deficiency, and an index of multiple parameters has been specifically described to this attend with various results …”
Section: Discussionmentioning
confidence: 99%
“…MicroR/%HypoHe ratio is not accurately enough to discriminate beta-thalassemia minor and iron deficiency, and an index of multiple parameters has been specifically described to this attend with various results. 17,18 To conclude, we propose a costless, easy-to-use screening approach highly efficient to detect HS and pyruvate kinase deficiencies using Sysmex analyzers. These screening tools produce substantially better results than using only one parameter (Tables S2 and S3).…”
Section: Discussionmentioning
confidence: 99%
“…Serum iron and ferritin dosages are good indicators of iron storage, enabling the early detection of iron deficiency. Nonetheless, in cases where ferritin levels are within the reference values or increased, other tests such as total iron binding capacity and transferrin saturation may help in better characterization of the type of anemia [30,31].…”
Section: Resultsmentioning
confidence: 99%